อุทกพลศาสตร์ของอนุภาคถ่านหินในเครื่องฟลูอิไดซ์เบดแบบหมุนเวียน - ปาจรีย์ ตั้งผดุงรัชต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
In this research, hydrodynamic of coal particle in circulating fluidized bed (CFB) was studied at room temperature in a visible acrylic reactor to detect particle movement. The effect of particle sizes and air flow rates on particle velocity and pressure in the CFB riser were studied. Pressure changed inside the reactor was used to calculate particle voidage. Particle velocity was recorded and computed by using CCD camera with Image Pro Plus Program technique. The average particle sizes were 400, 600, 800 and 1000 micron and the range of air flow rate was 400-700 l/min. The density of coal particle was 1380 kg/qb.m. It was found that at every air flow rate particle velocity and pressure inside the reactor decreased along the riser. At the same position, as the air flow rate increased the particle velocity increased. The voidage was found to decrease along the riser height except at the top of the reactor. The differences between particle velocity recorded from experiment and that calculated from linear regression equation were found to be the range of 20%.